Soil Quality Index and Its Determining Factors in Shrub Vegetation: Implications for Sustainable Land Management in Aceh Besar, Indonesia - Ruhalena Wilis; Umar Husein Abdullah (Postgraduate, University of Mataram, 2026)
Soil Quality Index (SQI) is an important indicator for evaluating soil functions and supporting sustainable land management. However, information on the relationships between SQI and soil properties under tropical shrub vegetation remains limited. This study aimed to analyze the correlation between SQI and selected soil physical and chemical properties under shrub vegetation in Aceh Besar Regency, Indonesia. Soil samples were collected using purposive sampling from shrubland sites and analyzed for nine soil variables, including rooting depth, silt and clay fractions, bulk density, porosity, soil pH, total nitrogen, available phosphorus, exchangeable potassium, and soil organic carbon. The SQI was determined using a scoring-based index approach, and Pearson correlation analysis was performed using IBM SPSS Statistics 25. The average SQI was 0.4381, indicating moderate soil quality. Soil physical properties were the primary determinants of SQI, with the silt and clay fractions showing the strongest positive correlation (r = 0.993), followed by porosity (r = 0.934) and rooting depth (r = 0.790). Among the chemical properties, exchangeable potassium exhibited the strongest positive correlation (r = 0.870). These findings indicate that improving soil physical conditions, particularly soil texture and porosity, while maintaining potassium availability, should be prioritized to enhance soil quality and support sustainable management of shrubland ecosystems in Aceh Besar Regency.